Hubungan Antara Kualifikasi Dokter Dengan Kerasionalan Penulisan Resep Obat Oral Kardiovaskuler Pasien Dewasa Ditinjau Dari Sudut Interaksi Obat (Studi Kasus di Apotek “x” Jakarta Timur) - Harianto, Harianto; Kurnia, Ridwan; Siregar, Syafrida (UI Scholars Hub, 2006)
The aim of this research is to reveal the relationship between the physician’s qualification and the rationality of the prescribing oral cardiovascular drugs to adult patients from drugs interactions point of view. This research is classified into descriptive analitic retrospectif survey. Data was collected from a dispensary located in East Jakarta. The result showed that rate of the rationality of prescribing cardiovascular agents by the physician’s is 89,86%. From total prescribing, 56,45% among them was prescribed by specialist whereas the rest 43,55% was prescribed by general practitioners. The rate of the irrational prescribing is 10,14%. From total prescribing, 78,57% among them was prescribed by general practitioners whereas the rest 21,43% was prescribed by specialist. Based on Chi square test’s result, there is a relationship between physician’s qualification and the rationality of the prescribing oral cardiovascular drug. Specialist physicians more rational compare to general practitioners in prescribing oral cardiovascular drug